Emibaru: Interactive E-Modules Based on Problem Solving Ability for Fifth Grade Students in Elementary School - Fery Muhamad Firdaus; Vaziana Qatrunnada Salmawati; Lenia Dwi Normayani (Jurnal Ilmiah Sekolah Dasar, 2024)
Creating meaningful learning is crucial to accommodate students’ problems solving ability development. This research is motivated by the low problem-solving ability of elementary school students in solving mathematical word problems, hence the need for teachers to make an effort in developing teaching materials for students to improve their mathematical problem-solving abilities. This study aims to develop a spatial interactive e-module (Emibaru) and evaluate the problem-solving abilities of 5th-grade students in using the interactive e-module. The quantitative approach and quasi-experimental method with a pretest-post-test control group design were applied in this research. The sampling technique was simple random sampling with 12 students from the experimental group and nine from the control group. Data collection techniques are interviews, observations, and tests. The instruments used were interview sheets, observation sheets, and essay tests. The data analysis technique used the T-test assisted by the SPSS 23 application. The results based on the T-test analysis showed t 2.237 and the value of Sig. (2-tailed) is 0.037 at df 19 < 0.05. It was stated that the spatial interactive e-module (Emibaru) influenced problem-solving mathematical competence in geometric materials (cubes and blocks).